2014
DOI: 10.1002/ppsc.201400137
|View full text |Cite
|
Sign up to set email alerts
|

A New Crystal Phase Molybdate Yb2Mo4O15: The Synthesis and Upconversion Properties

Abstract: A new upconversion nanocrystal phase Yb2Mo4O15:Er is developed by using a facile aqueous‐precipitation procedure combined with thermal annealing. Nanocrystals of Yb2Mo4O15 are exclusively synthesized, with particle sizes ranging from 1 to 20 nm. The optical properties are characterized and a high upconversion quantum yield is determined to be ≈1.3% at room temperature, under excitation of ≈500 mW cm−2 IR (975 nm). To the best of our knowledge, this is the first work concerning the synthesis of nanocrystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… eUCQY [ 192 ] Mo 4 O 15 :Yb 1.82 Er 0.18 NC thin film 1-20 nm (*Varied) - *>0.1 975 (*Gauss) ~0.5 ~1.3 (500–575) 2.6 A, B, C?,D?, H?, I, J C? iUCQY [ 193 ] NaGdF 4 : (18%)Yb 3+ ,(2%)Er 3+ @NaYF 4 CD in Toluene 5.5 [16] nm (Hexagonal) - *>0.1 980 (*Gauss) 100 ~0.22 (500-700) Extrapolated data 2.2 x10 −3 A, H, I, J H *eUCQY [ 135 ] SrLuF: (30.6%)Yb 3+ ,(2.9%)Er 3+ @SrLuF CD in Toluene 4.9 (L: ~11] nm (Face-centred cubic) - *>0.1 980 (*Gauss) 100 ~0.66 (500-700) Extrapolated data 6.6 x10 −3 A, H, I, J H *eUCQY [ 135 ] SrLuF: (30.6%)Yb 3+ ,(2.9%)Er 3+ @SrLuF CD in Toluene 4.9 (~16] nm (Face-centred cubic) - *>0.1 980 (*Gauss) 100 ~1 (500-700) Extrapolated data …”
Section: Reviewing the Ucqy Reporting And Measurement Techniques In The Literaturementioning
confidence: 99%
“… eUCQY [ 192 ] Mo 4 O 15 :Yb 1.82 Er 0.18 NC thin film 1-20 nm (*Varied) - *>0.1 975 (*Gauss) ~0.5 ~1.3 (500–575) 2.6 A, B, C?,D?, H?, I, J C? iUCQY [ 193 ] NaGdF 4 : (18%)Yb 3+ ,(2%)Er 3+ @NaYF 4 CD in Toluene 5.5 [16] nm (Hexagonal) - *>0.1 980 (*Gauss) 100 ~0.22 (500-700) Extrapolated data 2.2 x10 −3 A, H, I, J H *eUCQY [ 135 ] SrLuF: (30.6%)Yb 3+ ,(2.9%)Er 3+ @SrLuF CD in Toluene 4.9 (L: ~11] nm (Face-centred cubic) - *>0.1 980 (*Gauss) 100 ~0.66 (500-700) Extrapolated data 6.6 x10 −3 A, H, I, J H *eUCQY [ 135 ] SrLuF: (30.6%)Yb 3+ ,(2.9%)Er 3+ @SrLuF CD in Toluene 4.9 (~16] nm (Face-centred cubic) - *>0.1 980 (*Gauss) 100 ~1 (500-700) Extrapolated data …”
Section: Reviewing the Ucqy Reporting And Measurement Techniques In The Literaturementioning
confidence: 99%
“…Furthermore, the rare earth doped molybdates and tungstates also attract much attention for application in areas such as lasers9, scintillators10, upconverters11, and bio-imaging12 to mention just a few. This shows the versatility of molybdate and tungstate based compounds.…”
mentioning
confidence: 99%
“…This shows the versatility of molybdate and tungstate based compounds. Thus the research of these compounds is very intensive and new structures are reported every so often1113.…”
mentioning
confidence: 99%